Emerging trends in engineering, science and technology for society, energy and environment : proceedings of the International Conference in Emerging Trends in Engineering, Science and Technology (ICETEST 2018), January 18-20, 2018, Thrissur, Kerala, India /: proceedings of the International Conference in Emerging Trends in Engineering, Science and Technology (ICETEST 2018), January 18-20, 2018, Thrissur, Kerala, India. (2018) - Unknown
No abstract available